2010
DOI: 10.1126/scisignal.2000549
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic Signaling: A Fundamental Mechanism in Neutrophil Activation

Abstract: Efficient activation of neutrophils is a key requirement for effective immune responses. We found that neutrophils released cellular adenosine triphosphate (ATP) in response to exogenous stimuli such as formylated bacterial peptides and inflammatory mediators that activated receptors for Fcγ, interleukin-8, C5a complement, and leukotriene B4. The release of ATP in response to stimulation of the formyl peptide receptor (FPR) occurred through pannexin-1 hemichannels that colocalized with FPR and P2Y2 nucleotide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
241
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 182 publications
(249 citation statements)
references
References 45 publications
8
241
0
Order By: Relevance
“…Our previous work has shown that neutrophils possess a highly structured and tightly regulated purinergic signaling system that defines various aspects of chemotaxis [3,7,8,40]. Our present study revealed that MDA-MB-231 breast cancer cells possess a variant of this purinergic signaling system.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Our previous work has shown that neutrophils possess a highly structured and tightly regulated purinergic signaling system that defines various aspects of chemotaxis [3,7,8,40]. Our present study revealed that MDA-MB-231 breast cancer cells possess a variant of this purinergic signaling system.…”
Section: Discussionsupporting
confidence: 52%
“…Adenosine receptors comprise four different members: A1, A2a, A2b, and A3 receptors [2]. We have previously demonstrated a key role for A3 receptors in the regulation of neutrophil chemotaxis [3][4][5][6][7]. Specifically, we found that stimulation of neutrophils causes the release of cellular ATP.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…This cycle of cell recruitment is often self‐amplified and sustained in MI/R and leads to further cell necrosis, scar formation, and cardiac dysfunction 6, 7, 8, 9, 10, 11. Adenine nucleotides such as ATP and AMP are potent danger‐associated molecular patterns that trigger chemotactic migration, vessel wall adhesion, and pro‐inflammatory cytokine production by early infiltrating leukocytes such as neutrophils and macrophages 12, 13, 14, 15. However, these adenine nucleotides can be dephosphorylated to adenosine.…”
Section: Introductionmentioning
confidence: 99%